Distribution of Methylenetetrahydrofolate Reductase rs1801133 Polymorphism in a Turkish Professional Cyclist Cohort - ULUCAN, KORKUT (ANNALS APPLIED SPORT SCIENCE, 2018)
Background. The determination of the genetic endowment of athletic performance in sports is an important step in developing personal training sessions or nutritional supplements for success in sports. Information about the genetic parameters responsible for these metabolisms will help sport's scientist to develop new insights for better performance. Muscle metabolism is one of the key points in better personal athletic performance. Objectives. The aim of this study is to analyze the distribution of the methylenetetrahydrofolate reductase enzyme (MTHFR) rs1801133 (C677T) genotype and allele distribution in a Turkish professional cyclist cohort. Methods. There were 25 Turkish cyclists enrolled in the study. Peripheral blood used for DNA isolation and the conventional polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methodology were used for genotyping. Results. There were 14 (56%), 10 (40%) and 1 (4%) cyclist who had CC, CT, and TT genotypes, respectively. C allele was counted as 38 (76%), and T alleles as 12 (24%). 9 (50%) of the male cyclist had CC, 8 (44.4%) had CT and only 1 had TT (5.6%) genotypes. C allele was counted as 26 (72.2%), and the T allele as 10 (27.8%) in the male cyclists. In the females, the respective genotypes for CC and CT were 5 (71.4%) and 2 (28.6%). C allele was counted as 12 (85.7%) and T allele as 2 (14.3%). Conclusion. In our cohort, both of the two genders, the CC genotype and C allele were found to be higher when compared to the other genotypes and T allele. Larger prospective studies focusing on the influence of MTHFR rs1801133 polymorphism in athletic performance are required for confirmation of our findings.
Keywords: Athletic Performance; Epigenetic; Folic Acid; Sport Genomic; Supplement; METHYLATION